(untitled) (Swiss Medical Weekly, 2021)
The authors present the case of a 58-year-old man with the unique combination of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and, later on, haemophagocytic lymphohistiocytosis admitted to the intensive care unit. During his ICU stay the patient developed a variety of complications including acute respiratory distress syndrome, pulmonary embolism, right heart failure and suspected HLH leading to multiorgan failure and death. Despite the proven diagnosis of haemophagocytic lymphohistiocytosis, the excessively high ferritin levels of the patient did not seem fully explained by this diagnosis. Therefore, the authors want to highlight different causes of hyperferritinaemia in critically ill patients and underline the importance of differential diagnoses when interpreting continuously rising ferritin levels.